MAPPING OF BUSINESS EMPOWERMENT PROGRAM FOR MICRO, SMALL, AND MEDIUM ENTERPRISES (MSMES) ON RUMAH PENGUSAHA MALANG RAYA COMMUNITY - Tri Yulistyawati Evelina; Ayu Sulasari (Jurnal Al-Iqtishad, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a significant role in the economy country which develop. As big as 90 percent from entity business is an MSMEs that contributes to global labor absorption. In terms of labor absorption, MSMEs in Indonesia absorb more power Work If compared to with country ASEAN other. Realizing the importance role MSMEs then it is necessary empowerment efforts MSMEs in in order to accelerate regional and central economic development and increase the competitiveness of MSME products. Rumah Pengusaha Malang Raya or abbreviated as RPMR is one of the communities MSMEs Which is at in region Malang Raya, Indonesia (Malang City, Malang Regency and Batu City). The current RPMR community members number 100 (one hundred) members who are mapped out consisting of culinary, handicrafts, fashion, and merchant. With the large number of MSMES members. Based on these ideals, so that this community can develop and make a significant contribution to improving the economy in Malang City and generally in East Java, it is needed mapping Business Empowerment Program. Micro, Small and Medium Enterprises which will be used later as an initial step to strengthen coordination and synchronization in MSME development programs.